Principle and prerequisites of regenerative agriculture: a review - Hanifah, Vyta W.; Karolinoerita, Vicca; Cahyana, Destika; Minasny, Budiman (Indonesian Soil Science Society of South Sumatra in Collaboration With Soil Science Department, Sriwijaya University, 2025)
Regenerative agriculture has recently gained popularity as a promising approach to achieving sustainable agriculture and ensuring food security. This article reviews scientific papers published between 1986 and 2024, as well as popular media, including the documentary